Two-limit problems for almost semicontinuous processes defined on a Markov chain - Karnaukh, E. V.; Карнаух, Є. В. (Institute of Mathematics, NAS of Ukraine, 2007)
We consider almost upper-semicontinuous processes defined on a finite Markov chain. The distributions of functionals associated with the exit of these processes from a finite interval are studied. We also consider some modifications of these processes.